Sequential open-label study of the safety, tolerability, and pharmacokinetic interactions between dihydroartemisinin-piperaquine and mefloquine in healthy Thai adults - Hanboonkunupakarn, B; Van Der Pluijm, R; Hoglund, R; Pukrittayakamee, S; Winterberg, M; Mukaka, M; Waithira, N; Chotivanich, K; Singhasivanon, P; White, N; Dondorp, A; Tarning, J; et al. (American Society for Microbiology, 2019)
Artemisinin-based combination therapies (ACTs) have contributed substantially to the global decline in Plasmodium falciparum morbidity and mortality, but resistance to artemisinins and their partner drugs is increasing in Southeast Asia, threatening malaria control. New antimalarial compounds will not be generally available soon. Combining three existing antimalarials in the form of triple ACTs, including dihydroartemisinin (DHA)-piperaquine mefloquine, is a potential treatment option for multidrug-resistant Plasmodium falciparum malaria. In a sequential openlabel study, healthy Thai volunteers were treated with DHA-piperaquine (120 to 960 mg), mefloquine (500 mg), and DHA-piperaquine mefloquine (120 to 960 mg 500 mg), and serial symptom questionnaires, biochemistry, full blood counts, pharmacokinetic profiles, and electrocardiographic measurements were performed. Fifteen healthy subjects were enrolled. There was no difference in the incidence or severity of adverse events between the three treatment arms. The slight prolongation in QTc (QT interval corrected for heart rate) associated with DHA-piperaquine administration did not increase after administration of DHA-piperaquine mefloquine. The addition of mefloquine had no significant effect on the pharmacokinetic properties of piperaquine. However, coadministration of mefloquine significantly reduced the exposures to dihydroartemisinin for area under the concentration-time curve (22.6%; 90% confidence interval [CI], 33.1, 10.4; P = 0.0039) and maximum concentration of drug in serum (29.0%; 90% CI, 40.6, 15.1; P = 0.0079). Mefloquine can be added safely to dihydroartemisinin-piperaquine in malaria treatment. (This study has been registered at ClinicalTrials.gov under identifier NCT02324738.)